Structural plasticity in I-Ag7 links autoreactivity to hybrid insulin peptides in type I diabetes - Erausquin, Elena; Serra, Pau; Parras, Daniel; Santamaria, Pere; López-Sagaseta, Jacinto (Frontiers in Immunology, 2022)
We recently provided evidence for promiscuous recognition of several different hybrid insulin peptides (HIPs) by the highly diabetogenic, I-Ag7-restricted 4.1-T cell receptor (TCR). To understand the structural determinants of this phenomenon, we solved the structure of an agonistic HIP/I-Ag7 complex, both in isolation as well as bound to the 4.1-TCR. We find that HIP promiscuity of the 4.1-TCR is dictated, on the one hand, by an amino acid sequence pattern that ensures I-Ag7 binding and, on the other hand, by the presence of three acidic residues at positions P5, P7 and P8 that favor an optimal engagement by the 4.1-TCR’s complementary determining regions. Surprisingly, comparison of the TCR-bound and unbound HIP/I-Ag7 structures reveals that 4.1-TCR binding triggers several novel and unique structural motions in both the I-Ag7 molecule and the peptide that are essential for stable docking. This observation indicates that the type 1 diabetes-associated I-Ag7 molecule is structurally malleable and that this plasticity allows the recognition of multiple peptides by individual TCRs that would otherwise be unable to do so.